Obesity in the global haemophilia population: prevalence, implications and expert opinions for weight management. (6th September 2018) - Wilding, J.; Zourikian, N.; Di Minno, M.; Khair, K.; Marquardt, N.; Benson, G.; Ozelo, M.; Hermans, C.
Summary: Overweight and obesity may carry a significant disease burden for patients with haemophilia (PWH), who experience reduced mobility due to joint inflammation, muscle dysfunction and haemophilic arthropathy. This review aimed to define the prevalence and clinical impact of overweight/obesity in the global population of PWH. A detailed literature search pertaining to overweight/obesity in haemophilia in the last 15 years (2003–2018) was conducted, followed by a meta‐analysis of epidemiological data. The estimated pooled prevalence of overweight/obesity in European and North American PWH was 31%. Excess weight in PWH is associated with a decreased range in motion of joints, accelerated loss of joint mobility and increase in chronic pain. Additionally, the cumulative disease burden of obesity and haemophilia may impact the requirement for joint surgery, occurrence of perioperative complications and the prevalence of anxiety and depression that associates with chronic illness. Best practice guidelines for obesity prevention and weight management, based on multidisciplinary expert perspectives, are considered for adult and paediatric PWH. Recommendations in the haemophilia context emphasize the importance of patient education and tailoring engagement in physical activity to avoid the risk of traumatic bleeding.